Spironolactone promotes autophagy via inhibiting PI3K/AKT/mTOR signalling pathway and reduce adhesive capacity damage in podocytes under mechanical stress. Issue 4 (8th July 2016) - Li, Dong; Lu, Zhenyu; Xu, Zhongwei; Ji, Junya; Zheng, Zhenfeng; Lin, Shan; Yan, Tiekun
Abstract : Mechanical stress which would cause deleterious adhesive effects on podocytes is considered a major contributor to the early progress of diabetic nephropathy (DN). Our previous study has shown that spironolactone could ameliorate podocytic adhesive capacity in diabetic rats. Autophagy has been reported to have a protective role against renal injury. The present study investigated the underlying mechanisms by which spironolactone reduced adhesive capacity damage in podocytes under mechanical stress, focusing on the involvement of autophagy. Human conditional immortalized podocytes exposed to mechanical stress were treated with spironolactone, LY294002 or rapamycin for 48 h. The accumulation of LC3 puncta was detected by immunofluorescence staining. Podocyte expression of mineralocorticoid receptor (MR), integrin β1, LC3, Atg5, p85-PI3K, p-Akt, p-mTOR were detected by Western blotting. Podocyte adhesion to collagen type IV was also performed with spectrophotometry. Immunofluorescence staining showed that the normal level of autophagy was reduced in podocytes under mechanical stress. Decreased integrin β1, LC3, Atg5 and abnormal activation of the PI3K/Akt/mTOR pathway were also detected in podocytes under mechanical stress. Spironolactone up-regulated integrin β1, LC3, Atg5 expression, down-regulated p85-PI3K, p-Akt, p-mTOR expression and reduced podocytic adhesive capacity damage. Our data demonstrated that spironolactone inhibited mechanical-stress-induced podocytic adhesive capacity damage through blocking PI3K/Akt/mTOR pathway and restoring autophagy activity.